Effect of bismuth incorporation on thermal properties of quaternary chalcogenide glass Se80Te15-xCd5Bix (x=0, 5, 10) alloys. Issue 16 (November 2020) - Shoab, Mohd; Rahman, Raja Saifu; Aslam, Zubair; Zulfequar, Mohammad
Abstract: Differential scanning calorimetry has been employed to investigate the thermal properties of Se80 Te15-x Cd5 Bix (x = 0, 5, 10) glass system. The Variation of characteristic temperatures such as glass transition temperature (Tg ), onset crystallization temperature (Tc ), peak crystallization temperature (Tp ) and melting temperature (Tm ) are studied as a function of composition and heating rate. A stepwise increase in values of characteristic temperatures has been observed with the increase in heating rate. Further, obtained values of characteristic temperatures display decreasing trend with increase in bismuth concentration. The compositional and heating rate dependence of Thermal parameters such as glass forming ability (ΔT), thermal stability (Hg ), enthalpy (ΔH) and entropy (ΔS) has been investigated. It has been observed that ΔT and Hg have lowest and highest values for Se80 Te5 Cd5 Bi10 and Se80 Te15 Cd5 compositions respectively. Avrami index (n) and activation energy for crystallization (Ec ) have been calculated for all the samples. Values of n obtained for Se80 Te15 Cd5, Se80 Te15 Cd5 Bi5 and Se80 Te5 Cd5 Bi10 compositions are found to be 1.44, 2.16 and 2.16 respectively. Based on the obtained values of n, the nucleation process in alloys is discussed. It is noteworthy to mention that least value of Ec is observed for the alloy Se80 Te5 Cd5 Bi10 containing the highest amount of bismuth. Furthermore, calculated thermal parameters are used to anticipate the electrical switching behavior of the alloys.